Maternal depression is not just a problem early on. (August 2016) - Kothari, C.; Wiley, J.; Moe, A.; Liepman, M.R.; Tareen, R.S.; Curtis, A.
Abstract: Introduction: Little is known about the onset of depres s ion beyond the first postpartum year. This study examines the onset and course of depression over an 18 month period among a socio-economically diverse, community-wide sample of women. Materials & methods: A prospective longitudinal telephone survey of 249 women was conducted at two weeks, two months, six months and 18 months after delivery. Depression was measured using the Edinburgh Postnatal Depression Scale (EPDS), and onset was defined as the first EPDS score of 12+ on the 30-point scale. Temporal trends were assessed using generalized estimating equation (GEE) regression. Results: There was a significant temporal trend for EPDS scores decreasing until six months and then rebounding at 18 months; mean EPDS 5.5, 4.3, 4.2, and 4.9 at two weeks, two months, six months and 18 months respectively, GEE, P < .001. Depression onset followed a similar trend and was found to be 6.8%, 2.6%, 2.7% and 6.0% at two weeks, two months, six months and 18 months respectively, GEE, P = .068. The high scores of the early-onset group (mean 14.4 at two weeks) contributed to the early depression spike, while the high scores of the late-onset group (mean 13.9 at 18 months) contributed to the late spike. Conclusions: Two peaks of depression were identified, one early and one late. They appear to be the result of two processes: (1) elevated depression symptoms at two-weeks and again at 18 months postpartum experienced by the full sample and, thus, they may be a normal trend, and (2) onset of major depression by two sub-groups of women, one at each time period. Therefore, continued screening after one-year post delivery is indicated. Highlights: A longitudinal study of 249 postpartum women, with depression screening four times over an 18 month period. Two peaks of depression-onset: two-weeks and 18 months after delivery. Both time periods also significant for increased symptomology across the study sample. One of the first studies to identify a later depression peak, at the entry into toddlerhood.